Respuesta :
Answer:
1) [tex]a_{1y}=\frac{m_2 g sin \theta - m_1 g}{m_1 + m_2}[/tex]
2) See below
Explanation:
1)
The system of equations that we have in this problem is:
[tex]m_2 a_{2x}=T-m_2 g sin \theta[/tex] (1)
[tex]m_1 a_{1y}=T-m_1 g[/tex] (2)
[tex]a_{2x}=-a_{1y}[/tex] (3)
Here we want to solve the system for [tex]a_{1y}[/tex].
First of all, we isolate T from eq.(2):
[tex]T=m_1 a_{1y}+m_1 g[/tex]
And we substitute this expression into eq(1):
[tex]m_2 a_{2x}=(m_1 a_{1y}+m_1 g)-m_2 g sin \theta[/tex]
Solving for [tex]a_{2x}[/tex], we get
[tex]a_{2x}=\frac{(m_1 a_{1y}+m_1 g)-m_2 g sin \theta}{m_2}[/tex]
Now we can substitute this into eq(3):
[tex]\frac{(m_1 a_{1y}+m_1 g)-m_2 g sin \theta}{m_2}=-a_{1y}[/tex]
And re-arranging for [tex]a_{1y}[/tex] we find:
[tex](m_1 a_{1y}+m_1 g)-m_2 g sin \theta}=-m_2 a_{1y}\\a_{1y}(m_1+m_2)=m_2 g sin \theta - m_1 g\\a_{1y}=\frac{m_2 g sin \theta - m_1 g}{m_1 + m_2}[/tex]
2)
We see that this solution satisfies all special cases. In fact:
- If [tex]m_2=0[/tex], [tex]a_{1y}=\frac{0\cdot g sin \theta - m_1 g}{m_1 + 0}=\frac{-m_1 g}{m_1}=-g[/tex]
- If [tex]m_1 = m_2[/tex] and [tex]\theta=\frac{\pi}{2}[/tex], we get
[tex]a_{1y}=\frac{m_2 g sin \frac{\pi}{2} - m_2 g}{m_2 + m_2}=\frac{m_2 g-m_2 g}{2m_2}=0[/tex]
Also, this solution has dimensions of acceleration. In fact:
- The term at the numerator is in the form [tex]m*g[/tex], where mass is in kilograms and g is in meters per second squared (so, it is in the form mass*acceleration)
- The term at the denominator is a mass, so it is in kilograms
This means that [tex]a_{1y}[/tex] is (mass*acceleration)/(mass), therefore it has dimensions of acceleration.